2020
DOI: 10.1038/s41435-020-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Extra-adrenal glucocorticoid biosynthesis: implications for autoimmune and inflammatory disorders

Abstract: Glucocorticoid synthesis is a complex, multistep process that starts with cholesterol being delivered to the inner membrane of mitochondria by StAR and StAR-related proteins. Here its side chain is cleaved by CYP11A1 producing pregnenolone. Pregnenolone is converted to cortisol by the enzymes 3-βHSD, CYP17A1, CYP21A2 and CYP11B1. Glucocorticoids play a critical role in the regulation of the immune system and exert their action through the glucocorticoid receptor (GR). Although corticosteroids are primarily pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 292 publications
4
96
0
3
Order By: Relevance
“…GC synthesis and release are under the control of the hypothalamic–pituitary–adrenal neuroendocrine axis, which acts as a major regulator of skin integrity and function. In addition to the adrenal source of GCs, the skin can produce steroidogenic enzymes and extra-adrenal GCs, allowing for an immediate tissue-specific response 21 . Local GC synthesis occurs in both epidermis and dermis, and plays a major role in cutaneous homeostasis and pathological conditions 22 27 .…”
Section: Discussionmentioning
confidence: 99%
“…GC synthesis and release are under the control of the hypothalamic–pituitary–adrenal neuroendocrine axis, which acts as a major regulator of skin integrity and function. In addition to the adrenal source of GCs, the skin can produce steroidogenic enzymes and extra-adrenal GCs, allowing for an immediate tissue-specific response 21 . Local GC synthesis occurs in both epidermis and dermis, and plays a major role in cutaneous homeostasis and pathological conditions 22 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The data on lipocalin-2 and retinol binding protein (RBP)-4 are conflicting and further studies are required [12]. In addition, the adipose tissue has the capability of producing proopiomelanocortin (POMC) derived peptides with anti-inflammatory activities and is involved in glucosteroidogenesis [38,39].…”
Section: The Endocrine Function Of Adipose Tissue and Psoriasismentioning
confidence: 99%
“…It has been shown that the skin is a corticosteroidogenic organ with a capability for steroid synthesis starting from cholesterol. [5][6][7][8][9][10] Human hair follicles are also able to produce cortisol. [11] Synthetic corticosteroids, in use since 1950s, are the most prescribed drugs for treatment of skin diseases such as atopic dermatitis (AD), psoriasis, vitiligo, lichen planus and other inflammatory skin diseases and are not the focus of this review, for more details, please read specialized reviews.…”
Section: Corti Cos Teroidsmentioning
confidence: 99%